Local Brand, Loyal Customers: A Qualitative Study on Consumer Loyalty at Hisana Fried Chicken in 2025 - Guna, Kestu Galang; Cahyani, Leni (Manunggal Halim Jaya, 2026)
Customer loyalty in the increasingly competitive fast-food industry requires companies to focus not only on product quality but also on delivering excellent service, offering competitive pricing, and implementing effective promotional strategies. Hisana Fried Chicken, a local brand targeting lower-middle-class consumers, particularly students and workers, remains a popular choice despite facing competition from national brands and similar franchises. This study aims to identify the factors influencing customer loyalty toward Hisana Fried Chicken in 2025. The research employs a descriptive qualitative approach, utilizing data triangulation techniques that include in-depth interviews, participatory observation, and documentation. Informants consist of four individuals: two store managers and two active customers from Hisana Fried Chicken branches located in Bojongsoang and Sukabirus, Bandung. The findings reveal that customer loyalty is shaped by three key aspects: repeat purchase, long-term retention, and referrals. The main driving factors include affordable prices, consistent chicken flavor, fast and friendly service, and digital engagement through social media. These findings suggest that, in the context of a local brand, customer loyalty can be fostered not only through product excellence but also through emotional connection and a consistently positive consumer experience. This study provides valuable insights for fast-food business operators in building customer loyalty amidst intense competition and evolving consumer preferences.